The Analysis between the Diagnose of Preeclampsia and Eclampsia to Treatment at Dr. H. Jusuf SK Hospital Indonesia - Azizah, Shafira Aisyah; Wijayanti, Sari; Syuhada, Syuhada; Noviani, Doris (Baiman Bauntung Batuah Center, 2023)
Preeclampsia and eclampsia are types of gestational hypertension that are considered causes of maternal and perinatal death. Preeclampsia in severe conditions will result in eclampsia accompanied by symptoms of seizures or decreased consciousness. In the condition of preeclampsia, antihypertensive therapy is needed. The use of antihypertensives in patients with Preeclampsia and Eclampsia, namely methyldopa and labetalol, is the first line, and hydralazine, nifedipine, prazosin, and clonidine are the second line. The design of this study is a descriptive cross-sectional study to see the relationship between diagnoses and types of treatment. This research was conducted at Dr.H.Jusuf SK Hospital, Tarakan City, North Kalimantan Province, with secondary data from medical records as research data. The research subjects were pregnant women diagnosed with preeclampsia and eclampsia without accompanying comorbid diseases, with a sample of 49 respondents using a total sampling system. The results of this study found that one patient was diagnosed with Mild Preeclampsia with a single therapy, 45 patients were diagnosed with Severe Preeclampsia with a single therapy, a combination of 2 drugs and a combination of 3 drugs, and three patients were diagnosed with eclampsia with single therapy and a combination of 4 drugs. The data from this study showed a relationship between diagnosis and the type of treatment therapy with a significant value of 0.004 (p<0.05). The findings of this study can be used as a guide for medical therapy by healthcare professionals.